Effect of Green Accounting and Environmental Performance on Firm Value Moderated by Profitability - Salehah, Anggita Putri; Winda Ningsih; Fitri Syakinah (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2026)
This study examines how green accounting and environmental performance affect the value of companies listed on the Indonesia Stock Exchange from 2020-2024, using profitability as a moderating element. This research uses a quantitative approach, selecting 17 companies through purposive sampling. Annual reports, Sustainability Reports, and PROPER publications are used as secondary data. The study employs SmartPLS 3.2.9 for SEM-PLS method data analysis. The results show that green accounting has a negative and significant effect on firm value, while environmental performance and profitability have a positive and significant effect on firm value. Furthermore, profitability is proven capable of moderating the relationship between green accounting and firm value by strengthening its negative effect, but it does not moderate the relationship between environmental performance and firm value. These findings indicate that firm value is related to how companies manage environmental aspects as well as their financial performance